2011
DOI: 10.1523/jneurosci.5640-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neuronal Connexins 36 and 45 in Shaping Spontaneous Firing Patterns in the Developing Retina

Abstract: Gap junction coupling synchronizes activity among neurons in adult neural circuits, but its role in coordinating activity during development is less known. The developing retina exhibits retinal waves - spontaneous depolarizations that propagate among retinal interneurons and drive retinal ganglion cells to fire correlated bursts of action potentials. During development, two connexin isoforms, connexin36 (Cx36) and Cx45, are expressed in bipolar cells and retinal ganglion cells (RGCs), and therefore provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 88 publications
(153 reference statements)
8
54
1
2
Order By: Relevance
“…Cx36 is the most abundant retinal connexin and couples most ganglion cells to other ganglion or amacrine cells (25). Although cx36KO mice have an increase in asynchronous firing in between retinal waves, they exhibit cholinergic retinal waves with propagation patterns that are indistinguishable from WT during the first postnatal week (24,26). We found that β2-cx36 dKO mice did not exhibit recovered retinal waves in either the dark or light ( Fig.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Cx36 is the most abundant retinal connexin and couples most ganglion cells to other ganglion or amacrine cells (25). Although cx36KO mice have an increase in asynchronous firing in between retinal waves, they exhibit cholinergic retinal waves with propagation patterns that are indistinguishable from WT during the first postnatal week (24,26). We found that β2-cx36 dKO mice did not exhibit recovered retinal waves in either the dark or light ( Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Correlation index curves showed no difference in the dark and light for both WT and β2KO mice. We next used these correlation indices to construct connectivity maps, which show connections between neurons with the highest correlation indices (26,27). In particular, this strategy has been used in the developing hippocampus to identify highly connected hub neurons, which repeatedly initiate activity (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Fujihara et al, 2008;Kermer et al, 1999;Lynch, Dawson, 1994). Em relação à comunicação direta célula-célula, a concentração do cálcio parece ser particularmente importante, uma vez que é classicamente associado a apoptose no sistema nervoso, além disso, alterações rápidas na concentração de cálcio intracelular, causadas pelo acoplamento via JCs, foram claramente demonstrados na retina (Blankenship et al, 2011;Firth et al, 2005). A transferência de segundos mensageiros facilmente difusíveis por canais de JCs, como IP3, poderia controlar as concentrações de cálcio citosólico (Bosanac et al, 2002).…”
Section: Discussionunclassified
“…Em retinas de camundongos KO para a Cx36 e Cx45, apesar de ser observado o aumento do número de potenciais de ação ocorridos de maneira desincronizada, não foi notado a extinção completo da atividade, demonstrando que as Cx45 e Cx36 não são necessárias para a propagação das ondas retinianas. Curiosamente, a restrição da expressão de apenas um dessas Cxs não altera de forma significativa os padrões de propagação das ondas da retina (Blankenship et al, 2011).…”
Section: Jcs Durante O Desenvolvimento Do Sistema Nervoso De Roedoresunclassified